Evaluation of the reactivity of ultra-lean PRF/air mixtures by weak flames in a micro flow reactor with a controlled temperature profile. Issue 11 (2nd November 2018) - Grajetzki, P.; Nakamura, H.; Tezuka, T.; Hasegawa, S.; Maruta, K.
ABSTRACT: The reactivity of ultra-lean primary reference fuel (PRF)/air mixtures was investigated by weak flames in a vertical-type micro flow reactor (MFR) with a controlled temperature profile. In experiments, steady-separated weak flames were obtained at equivalence ratios between 0.5 and 1.0 for PRF80, 90, and 100. At leaner conditions, all the fuels showed hot flames at lower temperature regions, indicating higher reactivity. In one-dimensional steady simulations of the present micro flow reactor by modified Chemkin-Pro PREMIX, the LLNL PRF mechanism was able to reproduce the experimental tendency, while the KUCRS PRF mechanism showed the opposite trend. By analyzing major reactions leading to the hot flame, seven H–O reactions were identified that primarily control the hot flame response to a change of equivalence ratio. By exchanging the rate parameters of these seven reactions for more recent ones, the reactivity trend was brought to very good agreement with experimental results. This improvement was credited to a better spatial separation of intermediate- and high-temperature reactions in the MFR and emphasizes the strength of this investigation method.